Characterization of transcriptomic signature of primary prostate cancer analogous to prostatic small cell neuroendocrine carcinoma - Alshalalfa, Mohammed (Int J Cancer, 2019)
Prostatic small cell neuroendocrine carcinoma (SC/NE) is well studied in metastatic castration‐resistant prostate cancer; however, it is not well characterized in the primary setting. Herein, we used gene expression profiling of SC/NE prostate cancer (PCa) to develop a 212 gene signature to identify treatment‐naïve primary prostatic tumors that are molecularly analogous to SC/NE (SC/NE‐like PCa). The 212 gene signature was tested in several cohorts confirming similar molecular profile between prostatic SC/NE and small cell lung carcinoma. The signature was then translated into a genomic score (SCGScore) using modularized logistic regression modeling and validated in four independent cohorts achieving an average AUC >0.95. The signature was evaluated in more than 25,000 primary adenocarcinomas to characterize the biology, prognosis and potential therapeutic response of predicted SC/NE‐like tumors. Assessing SCGScore in a prospective cohort of 17,967 RP and 6,697 biopsy treatment‐naïve primary tumors from the Decipher Genomic Resource Information Database registry, approximately 1% of the patients were found to have a SC/NE‐like transcriptional profile, whereas 0.5 and 3% of GG1 and GG5 patients respectively showed to be SC/NE‐like. More than 80% of these patients are genomically high‐risk based on Decipher score. Interrogating in vitro drug sensitivity analyses, SC/NE‐like prostatic tumors showed higher response to PARP and HDAC inhibitors.